845 THE PREDICTIVE ROLE OF HIGH-SENSITIVITY CARDIAC TROPONIN T IN THE EMERGENCY ROOM: COMBINING BIOMARKERS WITH CLINICAL DATA LEADS TO THE DIAGNOSIS OF CARDIOVASCULAR DISEASE. (15th December 2022) - Golino, Michele; Marazzato, Jacopo; Blasi, Federico; Morello, Matteo; Chierchia, Valentina; Cadonati, Cristina; Ghirimorldi, Elena; Pellitteri, Alessia; Matteo, Federica; Licciardello, Claudio; Zappa, Martina; Ageno, Walter; et al.
Abstract: Background: Small amounts of high-sensitivity cardiac troponin (hs-cTn) I and T can be detected in healthy individuals or can occur in the absence of any clinical features of myocardial ischemia (myocardial injury). However, it is not possible to clinically distinguish whether and which increase in hs-cTn are due to which mechanisms. Moreover, predictive data regarding hs-cTnT in an emergency room (ER) setting are scanty. Consequently, with this monocentric retrospective study, we aimed at expanding the knowledge of this biomarker in this setting. Methods: Consecutive adult patients presenting at the ER and hospitalized with a first abnormal hs-cTnT value (≥14 ng/L) were enrolled for 6 months. The baseline hs-cTnT value and the ensuing variations were correlated with the clinical presentation and diagnosis. Subsequently, multivariable models were built to assess which clinical and laboratory variables most influenced hospital admissions. Results: At a first screening, 4660 patients were considered, and 4149 patients were enrolled ( Figure 1 ). Of these, 1555 (37.5%) had a first hs-cTnT ≥14 ng/L, and 1007 (65%) were hospitalized according to the following diagnoses: acute coronary syndrome (ACS, 182; 18%), non-ACS cardiovascular disease (337; 34%) and non-cardiovascular disease (487; 48%). Higher hs-cTnT values as well as significant hs-cTnT variations were found in the ACS group (p < 0.01). Furthermore, in the latter, the mean percentage of variation of hs-cTnT was higher, while it was intermediate in the non-ACS group, and low in those with non-cardiovascular disease (407.5%, 270.6% and 12.4%, respectively). Only syncope and CRP (OR: 0.08, 95% CI: 0.02–0.39, p <0.01 and OR: 0.9988, 95% CI: 0.9979–0.9998, p = 0.02, respectively) or CRP (OR: 0.9948, 95% CI: 0.9908–0.9989, p = 0.01) and NT-proBNP (OR: 1.0002, 95% CI: 1.0000–1.0004, p = 0.02) were independent predictors of a cardiovascular disease diagnosis. On the other hand, only chest pain (OR: 22.91, 95% CI: 3.97–132.32, p < 0.01) and eGFR (OR: 1.04, 95% CI: 1.004–1.083, p = 0.03) were significantly associated with the ACS diagnosis. Conclusion: In our study, differently from the investigated hs-cTnT, only clinical variables predicted hospitalizations in different patients' subgroups.